An annotated catalogue of the gamasid mites associated with small mammals in Asiatic Russia. The family Hirstionyssidae (Acari: Mesostigmata: Gamasina) - Vinarski, Maxim V.; Korallo-Vinarskaya, Natalia P. (Zootaxa, 2020)
This article represents the third (and last) part of the catalogue of ectoparasitic gamasid mites associated with small mammals in Asiatic Russia (Siberia and the Russian Far East). A total of 19 species of the genus Hirstionyssus Fonseca, 1948 are indexed, with data on their taxonomic position, nomenclature, host range, and distribution within the region. As a conclusion, a brief overview of fauna of ectoparasitic gamasid mites parasitising Micromammalia (except bats) of Asiatic Russia is given. In total, 71 mite species belonging to nine genera of three families (Haemogamasidae, Hirstionyssidae, Laelapidae) are recorded and divided among taxonomic and ecological groupings.